(untitled) (Research, Society and Development, 2021)
“Natural sciences and mathematics are dominated by men!” Statements like this led us to seek data that could refute or confirm it. For this reason, the present work presents an analysis of the percentage of education of students at the Federal Rural University of Rio de Janeiro in Physics, Licentiate and Bachelor’s Degree in Mathematics, Mathematics/Computer, Chemistry and Biology, between 1989 and 2015. The analysis of these data is not limited only to the exploration of the number of graduates, but also to the data related to the number of teachers, as we seek throughout the text to understand issues such as compatibility - or the lack of it between the numbers of women and men graduates and the current faculty of the analyzed courses. Along this route, the discrepancy of the results was shown, between the predominant gender of graduate students and professors in each of the courses, in an attempt to alert the reader to an exclusive process, based on gender (cisgender men and women), recurrent in academic levels following graduation.